2017
DOI: 10.1037/xan0000139
|View full text |Cite
|
Sign up to set email alerts
|

Do salient features overshadow learning of other features in category learning?

Abstract: Hundreds of associative learning experiments have examined how animals learn to predict an aversive outcome, such as a shock, loud sound, or puff of air in the eye. In this study, we reversed this pattern and examined the role of an aversive stimulus, shock, as a feature of a complex stimulus composed of several features, rather than as an outcome. In particular, we used a category learning paradigm in which multiple features predicted category membership and asked whether a salient, aversive feature would red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…However, overshadowing is also strongest when the overshadowing cue (A) is more salient than the overshadowed cue (X; Mackintosh, 1976), and in humans, increasing the salience of the blocked cue (X) has either resulted in less blocking (Denton & Kruschke, 2006) or more blocking (Le Pelley, Beesley, & Griffiths, 2014). Finally a recent report in category learning found facilitated learning of features by a salient feature, a result in line with potentiation rather than overshadowing (Murphy & Dunsmoor, 2017). Overall, salience does not seem to be a variable that allows us to predict whether competition between stimuli, or facilitation, is to be observed in any orderly way.…”
Section: Other Variablesmentioning
confidence: 81%
See 1 more Smart Citation
“…However, overshadowing is also strongest when the overshadowing cue (A) is more salient than the overshadowed cue (X; Mackintosh, 1976), and in humans, increasing the salience of the blocked cue (X) has either resulted in less blocking (Denton & Kruschke, 2006) or more blocking (Le Pelley, Beesley, & Griffiths, 2014). Finally a recent report in category learning found facilitated learning of features by a salient feature, a result in line with potentiation rather than overshadowing (Murphy & Dunsmoor, 2017). Overall, salience does not seem to be a variable that allows us to predict whether competition between stimuli, or facilitation, is to be observed in any orderly way.…”
Section: Other Variablesmentioning
confidence: 81%
“…In a systematic series of experiments, Bouton and colleagues (Bouton, Jones, McPhillips, & Swartzentruber, 1986;Bouton, Dunlap & Swartzentruber, 1987) manipulated the salience of target (X) and interacting (A) cues in flavour aversion learning, and found that potentiation is most apt to occur when the target stimulus X is weakly conditionable. However, overshadowing is also strongest when the overshadowing cue (A) is more salient than the overshadowed cue (X; Mackintosh, 1976), and in humans, increasing the salience of the blocked cue (X) has either resulted in less blocking (Denton & Kruschke, 2006) or more blocking (Le Pelley, Beesley, & Griffiths, 2014), and a recent report in category learning found facilitated learning of features by a salient feature, a result in line with potentiation rather than overshadowing (Murphy & Dunsmoor, 2017). Overall, salience does not seem to be a variable that allows us to predict whether competition between stimuli, or facilitation, is to be observed in any orderly way.…”
Section: Other Variablesmentioning
confidence: 93%
“…For instance, without explicit instructions to learn the contingencies in a task, Schmidt and De Houwer (2019) failed to observe overshadowing and blocking, even though both phenomena were observed in the same task when there was a direct instruction to learn contingenciessuggesting a critical role of the instructions. Similarly, cue competition effects have not been observed in category learning tasks (Bott et al, 2007;Murphy & Dunsmoor, 2017) or in systematic experiments using a contextual cuing paradigm (Beesley & Shanks, 2012).…”
mentioning
confidence: 98%
“…There are some instances of blocking experiments with contrasting outcomes: one study revealed that increasing the salience of the blocked cue protects it from blocking (Denton & Kruschke, 2006) and another showing the opposite, that is enhanced blocking when using a highly salient blocked (or target) cue (Le Pelley et al, 2014). Our studies provide a new piece of evidence in this line of research focusing on the overshadowing effect, suggesting that the relative salience of the elements of the compound has no clear effect on the magnitude of competition (also see Murphy & Dunsmoor, 2017). Despite the fact that we observed an advantage of the color compared to the symbol cues during training and more precise judgments during the test phase, we did not observe an effect of category in the magnitude of overshadowing.…”
Section: Discussionmentioning
confidence: 70%